The message of Kings : God is present - Olley, John W. (John William), 1938- (Downers Grove, Ill. : InterVarsity Press, 2011)
John Olley shows how the two books of Kings retell the past as preached history, addressing the exilic situation of the original readers. This in turn helps as we ask how they speak to us today. Within the account of paths leading to short-term success but ultimate failure, there are pointers of hope, of God's continuing purposes and promises, and of the people's response in the present. In rich and often surprising ways, the narrative in Kings is part of the history that has shaped, and will continue to shape, the faith and life of Christian believers. Everyday life, along with the turmoil of national and global events, is the arena in which God's people are called to worship, trust and obey him, and it is on aspects of this life that 1 and 2 Kings can throw light.--From publisher's description.
Solomon's reign (1 Kings 1-11) -- Division-the first 160 years (1 Kings 12:1-16:28) -- Elijah and kings (1 Kings 16:29-2 Kings 2:25) -- Elisha and individuals, kings and revolution (2 Kings 3-13) -- To the end of Israel (2 Kings 14-17) -- From trust to exile--to th end of Judah (2 Kings 18-25)
Includes bibliographical references.
Keywords: Bible. -- Commentaries